The subway as fourth place: anomie, flânerie and the "crush of persons". Issue 2 (3rd May 2020) - Benediktsson, Mike Owen; Tuckel, Peter; Milczarski, William; Caruso, Farimata; DeCurtis, Michelle; Gadtaula, Prahelika; Herman, Matt; MacDonald, Nicholas; Silipo, Nicholas; Singh, Daniell
Abstract: Sociologically speaking, what kind of place is the subway? If urbanism is defined as the experience of being surrounded by strangers, then the subway is a quintessentially urban space. But social scientists remain polarized in their views of this space, alternately describing the subway as an antisocial environment, a liminal "non-place", or a space of multicultural contact. In this paper, we describe the social life of the subway, analyzing an original data-set compiled through detailed observations of the behavior of more than 4, 000 passengers on the New York City subway system. We use logistic regression to model the factors that influence how passengers direct their gaze and configure their bodies while riding mass transit, and interpret our results with the help of "subway diaries" kept by 18 research subjects over the course of a week. Our findings help to reconcile conflicting images of social interaction in crowded transportation spaces: the subway is a "fourth place": a utilitarian space in which context-specific norms serve to flatten social distinctions, allowing a passive form of social contact constrained by the presence and prevalence of other passengers in the subway car.